An ICI suppression analysis testbed for harbor unmanned ground vehicle deployment - Nguyen, Tien Hoa (2019)
In recent years, intelligent transport system (ITS) applications with unmanned ground vehicles (UGV) have increased dramatically to improve the safety, efficiency, and unique services in low- to medium-range communication deployment. Orthogonal frequency division multiplexing (OFDM) is adopted as a modulation scheme for this communication system to combat fading. Unfortunately, because of possible high UGV speed, the orthogonality between subcarriers in OFDM signals is prone to intercarrier interference (ICI) caused by the Doppler spread. This paper discusses ICI suppression analysis using Universal Software Radio Peripheral (USRP) N210 under several Harbor transmission scenarios. Such communication links may contain line of sight (LoS) components in transmission. The channel is thus modeled as the well-known fast time varying path loss model. Furthermore, this paper derives the signal to interference ratio (SIR) and evaluates this parameter for several types of fading and Doppler spread shapes in UGV channels. Additionally, the paper presents a practical method for calculating the spectral efficiency of OFDM systems, with an example for actual implementation in UGV systems. Eventually, the testbed results indicate that the SIR will decrease if the maximum Doppler spread expands. In the Rician channel, it can be seen that the SIR depends on the maximum Doppler speed, the angle of arrival (AoA), and even the Rician element of the LoS component.